Perbandingan Tiga Metode Transformasi Agrobacterium Untuk Pencarian Gen-gen Terkait Toleransi Kekeringan Menggunakan Transposon Ac/Ds pada padi cv. Batutegi - Mulyaningsih, E. S.; Aswidinnoor, H.; Sopandie, D.; Ouwerkerk, P.B. F.; Nugroho, S.; Loedin, I.H. Salmet (Perhimpunan Biologi Indonesia, 2010)
ABSTRACTTransformation Strategy for Indonesian Indica Rice in Attempt to Discover Drought-TolerantRelated Genes Using of Transposon Ac/Ds. Attempt to identify, isolate the gene, and study forgene function for several agronomical traits have been done including some drought toleranttraits. Japonica rice cultivars have been used due to its higher efficiencies compared withindica cultivars. Two plasmids namely pNU400 and pUR224 were used to generate mutants ofthese cultivars (Batutegi dan Kasalath cultivars). Those plasmids contain an element calledActivator (Ac) and Dissociator (Ds) respectively. The pNU400 contains GFP (green flourescensprotein) as a selectable marker, whereas the pUR224 contains hygromycine resistant gene andgusA as a reporter gene. Each plasmid was transformed into rice genome of Batutegi andKasalath cultivars by Agrobacterium mediated transformation using three methods oftransformation (A, B and C). The transformation method A was not suitable for both cultivars,where none of plantlets were produced from pNU400 and pUR224 plasmids. The transformationmethod B produced some plantlets from the Kasalath cultivar only using pUR224 plasmid.The transformation method C was the best method to produce transgenic plants from bothcultivars (Batutegi and Kasalath), using both plasmids (pNU400 and pUR224). The PCR analysisshowed that 19 and 9 plants of Batutegi and Kasalath contained both gusA and hpt genesrespectively. None of those plants contained of gusA gene. Southern blot analysis revealed 3independent lines from Batutegi dan 7 independent lines from Kasalath. The integration of Actransposon was analyzed based on expression gfp gene when observed under UV dark reader.This research has proved that indica rice cultivars, especially the Batutegi cultivar of Indonesianorigin, could be transformed. The cultivar could be used as plant model for the indicatransformation.Key words: transformation, drought tolerant, indica rice, Ac/Ds transposons, Agrobacterium.